EXPLORING GENERATIONAL DIFFERENCES IN ATTITUDES TOWARD HUMAN-LIKE ROBOTS - Maria BARBUL; Irina BOJESCU; Miruna NICULESCU (Annals of the University of Oradea: Economic Science)
The rapid advancement of robotic technologies and artificial intelligence (AI) has sparked widespread interest and debate regarding their integration into various aspects of daily life. As robots become increasingly capable of performing tasks traditionally carried out by humans, understanding public perception of these technologies becomes crucial. The objective of this paper is to explore the generational differences in attitudes toward robots. While younger generations may be more open to the integration of robots into daily life, addressing the concerns of older generations will be crucial for widespread acceptance. This analysis highlights the importance of considering generational perspectives when developing and implementing robotic technologies in various sectors.